Influence of Dilution Upon the Ultraviolet-Visible Peak Absorbance and Optical Bandgap Estimation of Tin (IV) Oxide and Tin(IV) Oxde-Molybdenum(IV) Sulfide Solutions - Ong, Khai Chin; Lee, Weng Nam; Mohammad, Khalid *; Muhammad Amirul, Aizat Mohd Abdah *; Ohberg, Patrick; Lim, Ling Hong; Hayashi, Yasuhiko; Nishikawa, Takeshi; Yap, Yuenkiat (Taylor and Francis Group, 2024)
The study investigated the constraints associated with the dilution technique in determining the optical bandgap of nanoparticle dispersion and modified nanocomposites, utilizing ultraviolet-visible absorbance spectra and Tauc plot analysis. A case study involving SnO2 dispersion and SnO2-MoS2 nanocomposite solutions, prepared through the direct solution mixing method, was conducted to assess the implications of dilution upon the absorbance spectra and bandgap estimation. The results emphasize the considerable impact of the dilution technique on the measured optical bandgap, demonstrating that higher dilution factors lead to shift in bandgap values. Furthermore, the study highlights that dilution can induce variations in the average nanoparticle sizes due to agglomeration, thereby influencing bandgap estimation. In the context of nanocomposites, the interaction between SnO2 nanoparticles and exfoliated MoS2 nanosheets diminishes with increasing dilution, leading to the estimated optical bandgap being primarily attributable to SnO2 nanoparticles alone. These observations underscore the necessity for caution when employing the dilution technique for bandgap estimation in nanoparticles dispersion and nanocomposites, offering valuable insights for researchers and practitioners in the field.